Pendampingan Peningkatan Budaya Literasi Dengan Pengadaan Perpustakaan Desa Di Desa Sooko Kecamatan Wringinanom Kabupaten Gresik - Muhamad Arif; Nurul Qomariyah; Lina Hanivia; Safitri Armarifah; Sintia Elia Agustin (LPPM, STAI Al-Azhar Menganti, 2022)
Community empowerment related to literacy through village libraries aims to increase or increase interest in reading, especially in children in order to develop their potential so that children who are used as future faces of the nation become superior seeds of intelligent and quality human beings because they are knowledgeable and have good morals as a result of education. the good one. The research method used is the ABCD (Asset Based Community Development) method. This method is an approach to community development. There are 5 procedures used in the ABCD method, namely Define, Discovery, Dream, Design, and Deliver/destiny. This community empowerment program can be implemented properly and maximally. The results showed that books that were used as Reading Corners and village libraries had a positive impact in overcoming various educational problems in Sooko village, Wringinanom Gresik, where at first the literacy culture in the community was still relatively low and was increasing day by day.